Antibiotics modulate biofilm formation in fish pathogenic isolates of atypical Aeromonas salmonicida - Desbois, Andrew P (Journal of fish diseases, 2020)
© 2020 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.